The Largest Stock Exchanges In The World And Their Listing Requirements: Best Practices For The Tashkent Stock Exchange (Eurasian Research Bulletin, 2024)
This article examines the London, New York, NASDAQ, Hong Kong, and Frankfurt stock exchanges, which are among the world's largest stock exchanges, their history of creation, and their place in the world market. Also, the positive aspects of the membership of The World Federation of Exchanges regarding the improvement of the activity of the Tashkent Stock Exchange were highlited.